Bank ownership and cost efficiency in Russia, revisited - Mikhail Mamonov; Andrei Vernikov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
This paper considers the comparative efficiency of public, private, and foreign banks in Rus-sia, a transition economy with several unusual features. We perform stochastic frontier anal-ysis (SFA) of Russian bank-level quarterly data over the period 2005–2013. The method of computation of comparative cost efficiency is amended to control for the effect of revalua-tion of foreign currency items in bank balance sheets. Public banks are split into core and other state-controlled banks. Employing the generalized method of moments, we estimate a set of distance functions that measure the observed differences in SFA scores of banks and bank clusters (heterogeneity in risk preference and asset structure) to explain changes in bank efficiency rankings. Our results for comparative Russian bank efficiency show higher efficiency scores, less volatility, and narrower spreads between the scores of different bank types than in previous studies. Foreign banks appear to be the least cost-efficient market participants, while core state banks on average are nearly as efficient as private domestic banks. We suggest that foreign banks gain cost-efficiency when they increase their loans-to-assets ratios above the sample median level. Core state banks, conversely, lead in terms of cost efficiency when their loans-to-assets ratio falls below the sample median level. The presented approach is potentially applicable to analysis of bank efficiency in other dollarized emerging markets.
URN:NBN:fi:bof-201508181357
Keywords: G21; P23; P34; P52; 330